THE INFLUENCE OF SALARY, INCENTIVES AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE (CASE STUDY ON PROPERTY DEVELOPER PT. PUTRA RIMBU SEJATI DEMAK) - eka sekar ayu ramadhani; Aris Puji Purwatiningsih; Nanda Adhi Purusa; Mochammad Eric Suryakencana Wibowo (Journal of Social and Economics Research, 2025)
Problems including salary delays, uneven incentives, and frequent employee lateness to work occur at PT Putra Rimbu Sejati Demak. This research aims to determine the effect of salary, incentives, and work discipline on employee performance at PT Putra Rimbu Sejati Demak. This research used quantitative methods with a saturated sample of 80 employees. Primary data was collected through questionnaires and analyzed using descriptive statistical tests, instrument tests, classical assumption tests, multiple linear regression, and hypothesis testing with IBM SPSS version 27. The results showed that salary, incentives, and work discipline partially and simultaneously had a positive and significant effect on employee performance. The coefficient of determination (R2) of 0.562 indicates that 56.2% of variation in employee performance is explained by these three variables. This research is expected to help companies improve HR management